Evaluation of the Impact of Health Sector Services fund on the Quality of Maternity Services at the Health Centres in Kisii South Sub-county, Kisii County, Kenya - Okatch, Jeremiah Oloo (JOOUST, 2017)
The Ministry of Health is the major financier of Public Health Services and previously the Ministry of Health used to disburse funds to the sub-counties through the sub¬county treasury. However, the health facilities were not accessing all quarterly funds on time due to operational chal!enges. It is against this background that the Ministry of Health adopted an innovative approach in 2005 that enables funds to be credited directly into the bank accounts of health facility bypassing the sub-county treasury. The approach was rolled out in the rest of the country in 2010 after successful piloting in coast region in Kenya. Since then no evaluation has been carried out to assess the impact of the approach. A descriptive study design was adopted to assess the impact of the direct funding on the quality of deliveries, improvement on quality of services and to identify some structural barriers to service delivery. The locations of the study were the Riotachi, Riana and Nyamagundo health centres in Kisii South Sub-County. They were chosen purposively. Data collection involved collecting secondary data from the maternity registers and interviewing health workers. Records of all deliveries two years before and two years after HSSF were collected. Paired student t-test at 95% Confidence Interval of SPSS version 16.0 was used to compare the mean values of deliveries before and after HSSF. Bar graphs were used to present summary statistics for qualitative variables collected. The results showed that the direct funding had a positive impact as there was a statistically significant increase (p=0.05) in the number of deliveries after introduction of HSSF. The mean of number of deliveries before and after HSSF were 195.667(SD=31.392) and 429.000 (SD=75.319) respectively. All health facilities were receiving HSSF, had HFMCs, CUs (100%) and a positive opinion on impact of HSSF. Only one facility (33%) had adequate staffing level. Medical supplies were adequate in only one facility (33%). The structural barriers like distance and means of transport were identified. Only one facility (33%) was conducting outreach services and had adequate stocks of medical supplies. Staffing challenges were there in all (100%) and the structural barriers to access to maternity services were identified in all (100%) the facilities. The recommendations are that the funding should be enhanced and it should be workload based. There is need to establish Community Ambulance referral system to mitigate the structural barriers.